A targeted approach of employing nano-materials in high-volume fly ash concrete. (November 2019) - Du, Sen; Ge, Yong; Shi, Xianming
Abstract: Unlike the conventional method of admixing nanomaterials directly in fresh high-volume fly ash (HVFA) concrete, this laboratory study explored a more targeted approach. Specifically, nanomaterials were used to improve the interface between coarse aggregate and paste, by coating the coarse aggregate with a cement paste that contained graphene oxide or nanosilica. Using such coated coarse aggregate, the mechanical and transport properties of HVFA concrete were investigated to evaluate the effect of nano-modified cementitious coating on the interfacial transition zone of concrete. The compressive and splitting strengths of HVFA concrete at 3, 7, 14, and 28 days and the water sorptivity and chloride migration coefficient at 28 days were measured. The results reveal that the nanomaterials paste-coated coarse aggregate can increase the strengths of HVFA concrete, while improving the transport properties of HVFA concretes (e.g., reducing their permeability). In addition, the resistance to freezing/thawing cycles was improved to a satisfactory level when incorporating the coated coarse aggregate in the HVFA concrete, even without air entrainment. Examination by scanning electron microscope/energy dispersive X-ray spectroscopy of the concrete samples led to a more comprehensive and mechanistic understanding of the nanomaterial-based coating.